A3 Adenosine Receptor Agonist Inhibited Survival of Breast Cancer Stem Cells via GLI‐1 and ERK1/2 Pathway. Issue 9 (3rd May 2017) - Jafari, Seyyed Mehdi; Panjehpour, Mojtaba; Aghaei, Mahmoud; Joshaghani, Hamid Reza; Enderami, Seyed Ehsan
ABSTRACT: Numerous studies have demonstrated the role of A3 adenosine receptor (A3AR) and signaling pathways in the multiple aspects of the tumor. However, there is a little study about the function of A3AR in the biological processes of cancer stem cells (CSCs). CSCs have a critical role in the maintenance and survival of breast cancer. The aim of current study was to investigate the effect of A3AR agonist on breast cancer stem cells (BCSCs). XTT assay showed antiproliferative effect of A3AR agonist (Cl‐IB‐MECA) on BCSCs. Our results also demonstrated that A3AR agonist reduces mammosphere formation in a dose‐dependent manner. Flow cytometry analysis showed that A3AR agonist induces G1 cell cycle arrest and apoptosis in BCSCs. Western blot assay showed that A3AR agonist inhibits the expression of cell cycle and apoptotic regulatory proteins as well as the expression of ERK1/2 and GLI‐1 proteins. Finally, these findings propose that A3AR agonist induces cell cycle arrest and apoptosis in BCSCs by inhibition of ERK1/2 and GLI‐1 cascade. J. Cell. Biochem. 118: 2909–2920, 2017. © 2017 Wiley Periodicals, Inc. Abstract : In this study, we found that A3 adenosine receptor agonist reduces survival of breast cancer stem cell by induction of cell cycle arrest and apoptosis. This study demonstrated that A3 adenosine receptor inhibits the BCSCs proliferation via Hedgehog‐GLI‐1 signaling.